Pengaruh Pengalaman, Biaya Operasional Dan Hasil Tangkapan Terhadap Pendapatan Nelayan Purse Seine Di Desa Pejala Pagatan Kecamatan Kusan Hilir Kabupaten Tanah Bumbu - Shaleha; Khairi Pahlevi (PPJP ULM, 2020)
This research was conducted in the village Pejala Pagatan, Kusan HilirSubdistrict, Tanah Bumbu District to know (1) to find out whether the experience,operational costs, and catch results factors together affect the income of Purse Seinefishers in the village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District ;(2) to find out what factors most influence the income of Purse Seine fishers in thevillage Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District.In this study, Respondents were 20 fishermen in the village of Purse Seinefishers in Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District. Data isprocessed using multiple regression analysis, hypothesis testing, and classicalassimilation tests.The results showed that jointly the experience, operational costs, and Catchesaffect the income of purse seine fishery in Purse Seine fishers' village in the villagePejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District. The Catches variable(X3) is the factor that most influences the income of the town of Purse Seine fishers inthe village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District.